Uso del e-marketing para la venta de paquetes turísticos de la empresa sacha runa Tarapoto – San Martín - Gonzáles Choy, Bryan Wilter (2015)
Sale of tourist packages of the company SachaRuna Tarapoto - San Martin using the EMarketing, studies the problem of poor sales of tour packages SachaRuna company that has over the competition by improper use of use web technologies and not having a solid, reliable and concise presence in Internet to disseminate updated their products, services and news of the San Martin region information. The e-marketing (set of strategies, techniques and operations coordinated through Internet, seeking to increase sales of its products and services) was used in research as a strategic tool to improve sales of package tours in the company SachaRunaTarapoto - San Martin. The population used were local, national and foreign located in the city of Tarapoto tourists; some of these tourists was sampled first pre survey was conducted after releasing the tourist information in a traditional way, then a post survey was conducted after the tourist information dissemination with encouragement variable "Using the EMarketing" implementing a website CMS platform. This was done in order to assess the quality of the website of the company SachaRuna. Data for hypothesis testing were obtained from the record sales of tourist packages period July to December 2014 and January to April 2015, which showed that the use of E - Marketing generates an improvement in sales of tour packages Company SachaRunaTarapoto - San Martin.